Валькирия. Тот, кого я всегда жду - Семенова Мария Васильевна (Миры Марии Семеновой, 2014)
Экземпляры: ф.6 (20230406) / Инвентарный номер: 3910zzz / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: С 30 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44